Developing an infant feeding core outcome set for childhood obesity prevention. (November 2018) - Matvienko-Sikar, Karen; Byrne, Molly; Kelly, Colette; Toomey, Elaine; Hennessy, Marita; Devane, Declan; Heary, Caroline; Harrington, Janas; Hayes, Catherine; Queally, Michelle; Kearney, Patricia M
Abstract: Background: Modifiable parental feeding behaviours are implicated in the development of childhood obesity. A lack of outcome standardisation across trials of infant feeding interventions limits examination of intervention effects and mechanisms of change. Core outcome sets (COS) are an agreed-upon minimum set of outcomes that should be measured in trials of a specific health condition. The aim of this research was to develop an infant feeding core outcome set to be evaluated in trials of infant feeding interventions to prevent childhood obesity. Methods: Development of the infant feeding COS was conducted in four stages. First, a systematic review identifying all infant feeding outcomes in the extant literature was done. The databases Embase, Medline, CINAHL, CENTRAL, and PsycINFO, were searched for English-language papers, from database inception to Feb 1, 2017, using search terms related to infants (eg, infant), early feeding (eg, complementary feeding), and study design (eg, randomised controlled trial, cohort). Second, a small-group expert stakeholder meeting was held to clarify and discuss identified outcomes. Third was an international e-Delphi outcome prioritisation survey. Fourth, a consensus meeting of expert stakeholders was held. Expert stakeholders included researchers, health-care professionals, parents, and child-care professionals. Findings: The systematic review identified 82 infant feeding outcomes. Outcomes were discussed and clarified with 13 stakeholders at the small-group meeting. The e-Delphi study was completed by 79 international stakeholders who rated outcomes for importance of inclusion in the COS. Seven expert stakeholders participated in the consensus meeting. 26 of the identified outcomes from the following nine domains were identified as crucial for inclusion in the COS: breast and formula feeding, introduction of solids, parent feeding practices and styles, parent knowledge and beliefs, practical feeding, food environment, dietary intake, perceptions of infant behaviour and preferences, and child weight outcomes. Interpretation: The developed COS is the minimum that should be measured and reported in trials of infant feeding interventions to prevent childhood obesity. Use of this COS will facilitate better synthesis and understanding of intervention effects and is essential to inform development and evaluation of future infant feeding interventions to prevent childhood obesity. Funding: Health Research Board Interdisciplinary Capacity Enhancement Award 2015-1026, Irish Research Council New Foundations Award, Health Research Board Trials Methodology Research Network Summer Student Scholarship.